2012
DOI: 10.1186/1471-230x-12-63
|View full text |Cite
|
Sign up to set email alerts
|

A frequent variant in the human bile salt export pump gene ABCB11 is associated with hepatitis C virus infection, but not liver stiffness in a German population

Abstract: BackgroundThe human ATP-binding cassette, subfamily B, member 11 (ABCB11) gene encodes the bile salt export pump, which is exclusively expressed at the canalicular membrane of hepatocytes. A frequent variant in the coding region, c.1331 T > C, leading to the amino acid exchange p.V444A, has been associated with altered serum bile salt levels in healthy individuals and predisposes homozygous carriers of the [C] allele for obstetric cholestasis. Recently, elevated bile salt levels were shown to be significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A common variant (p.A444V) of the hepatocanalicular BSEP (ABCB11) is associated with significant reduction in response rates for patients infected with HCV genotypes 2 and 3 compared with wild‐type carriers; a weaker association was found for genotype 1 . Consistent with these findings, two other studies showed that this variant was associated with HCV positivity in 206 and 649 patients, respectively. These data suggest that decreased BSEP expression in patients harbouring the p.A444V variant may lead to increased intracellular bile acid levels, which in turn may enhance viral replication via FXR.…”
Section: Chronic Viral Hepatitismentioning
confidence: 58%
“…A common variant (p.A444V) of the hepatocanalicular BSEP (ABCB11) is associated with significant reduction in response rates for patients infected with HCV genotypes 2 and 3 compared with wild‐type carriers; a weaker association was found for genotype 1 . Consistent with these findings, two other studies showed that this variant was associated with HCV positivity in 206 and 649 patients, respectively. These data suggest that decreased BSEP expression in patients harbouring the p.A444V variant may lead to increased intracellular bile acid levels, which in turn may enhance viral replication via FXR.…”
Section: Chronic Viral Hepatitismentioning
confidence: 58%
“…Measuring liver stiffness with TE is an effective, non-invasive, reproducible and currently well-established method to assess liver fibrosis [28,46,47]. Several studies have previously described associations between genetic variants and various liver diseases, using transient elastography as phenotype [48][49][50][51][52][53][54][55][56]. We used a cut-off of 8.0 kPa for clinically relevant liver fibrosis, as proposed and validated in previous community-based studies [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 649 HCV-infected patients and 413 controls, risk allele C carriers were overrepresented, but liver stiffness was not associated according to ABCB11 1331 genetic variants [96]. No significant association between ABCB11 polymorphism and prevalence of cirrhosis either in patients with nonalcoholic fatty liver disease (NASH) [89] or in a population with alcoholic liver disease [97] could be identified.…”
Section: Host Genetics and Chronic Complications Such As Fibrosis mentioning
confidence: 99%